2021
DOI: 10.1017/s1742170521000442
|View full text |Cite
|
Sign up to set email alerts
|

Toward greater sustainability: how investing in soil health may enhance maize productivity in Southern Africa

Abstract: Climate change and soil fertility decline are major threats to smallholder farmers' food and nutrition security in southern Africa, and cropping systems that improve soil health are needed to address these challenges. Cropping systems that invest in soil organic matter, such as no-tillage (NT) with crop residue retention, have been proposed as potential solutions. However, a key challenge for assessing the sustainability of NT systems is that soil carbon (C) stocks develop over long timescales, and there is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…A recent study by Mhlanga et al [ 22 ] showed that mulching is important in cropping systems of southern Africa as it serves as a source of organic matter for increased microbial activity as well as conserving moisture. This was also confirmed by Thierfelder et al [ 53 ]. Since the CPM-L system had no mulch, organic matter build-up, moisture conservation and soil temperature regulation in this system were not enhanced as compared to the CA-based systems.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study by Mhlanga et al [ 22 ] showed that mulching is important in cropping systems of southern Africa as it serves as a source of organic matter for increased microbial activity as well as conserving moisture. This was also confirmed by Thierfelder et al [ 53 ]. Since the CPM-L system had no mulch, organic matter build-up, moisture conservation and soil temperature regulation in this system were not enhanced as compared to the CA-based systems.…”
Section: Discussionsupporting
confidence: 84%
“…However, pH was high under CT relative to CA practices (NT, MT, and RT). (NIGUSSIE et al, 2021a;SITHOLE -MAGWAZA, 2019) obtained low TN under CT relative to MT and a low C: N ratio under MT compared to CT. High NO -3 -N, C: N ratio, TN, and NH + -N were observed under NT compared to CT (CHAUKE et al, 2022;THIERFELDER et al, 2022).…”
Section: Plant Nutrientsmentioning
confidence: 99%
“…SOC has been widely cited as a key indicator of soil quality (THIERFELDER et al, 2022). It is the earliest soil component to succumb to erosion and strangely the most difficult to restore, presenting significant challenges to modern farming (CHOWANIAK et al, 2020).…”
Section: Socmentioning
confidence: 99%
“…Saharan Africa (SSA) is on the frontline of climate change, and technologies are urgently needed for this region that couple sustainable crop production combined with greater soil fertility and continuous protection of the soil resource, with enhanced resilience to climate induced changes in local conditions (3). Soils supporting food production in this region are often degraded, with 25% (350 million ha) of the total land area falling under this category (4), and characterised by poor structure, light texture and low (and declining) soil organic matter (SOM) content, often resulting from continuous conventional agriculture practices (tillage, crop residue removal, mono-cropping) (5,6).…”
mentioning
confidence: 99%